PARTIAL CRYSTALLIZATION OF MID-OCEAN RIDGE BASALTS IN THE CRUST AND MANTLE - Herzberg C. (My University, 2004)
Pressures at which partial crystallization occurs for mid-ocean ridge basalts (MORB) have been examined by a new petrological method that is based on a parameterization of experimental data in the form of projections. Application to a global MORB glass database shows that partial crystallization of olivine + plagioclase + augite ranges from 1 atm to 1·0 GPa, in good agreement with previous determinations, and that there are regional variations that generally correlate with spreading rate. MORB from fast-spreading centers display partial crystallization in the crust at ridge segment centers and in both mantle and crust at ridge terminations. Fracture zones are likely to be regions where magma chambers are absent and where there is enhanced conductive cooling of the lithosphere at depth. MORB from slow-spreading centers display prominent partial crystallization in the mantle, consistent with models of enhanced conductive cooling of the lithosphere and the greater abundance of fracture zones through which they pass. In general, magmas that move through cold mantle experience some partial crystallization, whereas magmas that pass through hot mantle may be comparatively unaffected. Estimated pressures of partial crystallization indicate that the top of the partial melting region is deeper than about 20–35 km below slow-spreading centers and some ridge segment terminations at fast-spreading centers.